Voiz . The Orator - Razykov, Yusup (Uzbekfilm, 1998)
Duration: 00:55:00 In a playful and slightly ironical way, the film conveys the history of the establishement of Soviet power in Uzbekistan. Irony notwithstanding, the plot is based on the cruel stories about the so-called "Hudjum" movement that persecuted Uzbek women who staunchly refused to renounce the wearing of traditional veils. The director fashions his story as a kind of Oriental fairytale about a poor arbakesh who happened to have three wives, and shortly thereafter, acquired a fourth one. In order to protect his wives from the new power, he, being a talented public orator, becomes a staff agitator - "the voice" of the Soviet authorities. But the cruel epoch crushes him all the same and ruins the lives of his wives.